2009
DOI: 10.1007/s00438-009-0427-9
|View full text |Cite
|
Sign up to set email alerts
|

Plc1p is required for proper chromatin structure and activity of the kinetochore in Saccharomyces cerevisiae by facilitating recruitment of the RSC complex

Abstract: High-fidelity chromosome segregation during mitosis requires kinetochores, protein complexes that assemble on centromeric DNA and mediate chromosome attachment to spindle microtubules. In budding yeast, phosphoinositide-specific phospholipase C (Plc1p encoded by PLC1 gene) is important for function of kinetochores. Deletion of PLC1 results in alterations in chromatin structure of centromeres, reduced binding of microtubules to minichromosomes, and a higher frequency of chromosome loss. The mechanism of Plc1p's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In vivo chromatin crosslinking and immunoprecipitation were performed as described previously 59,61,64 with the following antibodies: anti-myc polyclonal antibody A-14, anti-HA monoclonal antibody F7, anti-Yap1p polyclonal antibody (all Santa Cruz Biotechnology), and anti-RNA polymerase II monoclonal antibody 8WG16 (Covance). Primers used for real-time PCR analysis are as follows: POL1 (5’-TCCTGACAAAGAAGGCAATAGAAG-3’and 5’-TAAAACACCC TGATCCACCTCTG -3’), FLR1 promoter (5’-AATGGGCGGGATAATTAGTCAG-3’ and 5’-GTGTGTCTGTACGTT GAAGTGTATACC-3’), FLR1 , middle of the coding region (5’-GTTGGTTGTGCTACTGT GCATAAC-3’ and 5’-AAACGAGAGGAACCATTTCTGG-3’), FLR1 , 3’ end of the coding region (5’-TACCCAAAGTATGTTGCATCCG-3’ and 5’-CCATGCCACAGGATAGTTCTT AGT-3’), PHO5 (5’-CCATTTGGGATAAGGGTAAACATC-3’ and 5’-AGAGATGAAGCCATACTAACCTCG -3’), GAL1 (5’-CGCTTAACTGCTCATTGCTATATTG-3’ and 5’-TTGTTCGGAGCAGTGCGG-3’), TRX2 (5’-ATACGACAGTGCTTTAGCATCTGG-3’ and 5’-GTTCTGCAAACTTTTCAATCATTG-3’), BNA1 (5’-GCGTCAGGATAAATTGTGAGTCAC-3’ and CCTTCGTTCTCCTTCAACCATTTG-3’), HSP12 (5’-AAGCACTCTAGACGGAGAGTAACTAG-3’ and 5’-GAATCCTTTTCTACCTGCGTCAG-3’), HSP26 (5’-CGGATCTATGCACGTTCTTGAGTG-3’ and 5’-CCTTCACCCAGCAATCTGTTAAAG-3’).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo chromatin crosslinking and immunoprecipitation were performed as described previously 59,61,64 with the following antibodies: anti-myc polyclonal antibody A-14, anti-HA monoclonal antibody F7, anti-Yap1p polyclonal antibody (all Santa Cruz Biotechnology), and anti-RNA polymerase II monoclonal antibody 8WG16 (Covance). Primers used for real-time PCR analysis are as follows: POL1 (5’-TCCTGACAAAGAAGGCAATAGAAG-3’and 5’-TAAAACACCC TGATCCACCTCTG -3’), FLR1 promoter (5’-AATGGGCGGGATAATTAGTCAG-3’ and 5’-GTGTGTCTGTACGTT GAAGTGTATACC-3’), FLR1 , middle of the coding region (5’-GTTGGTTGTGCTACTGT GCATAAC-3’ and 5’-AAACGAGAGGAACCATTTCTGG-3’), FLR1 , 3’ end of the coding region (5’-TACCCAAAGTATGTTGCATCCG-3’ and 5’-CCATGCCACAGGATAGTTCTT AGT-3’), PHO5 (5’-CCATTTGGGATAAGGGTAAACATC-3’ and 5’-AGAGATGAAGCCATACTAACCTCG -3’), GAL1 (5’-CGCTTAACTGCTCATTGCTATATTG-3’ and 5’-TTGTTCGGAGCAGTGCGG-3’), TRX2 (5’-ATACGACAGTGCTTTAGCATCTGG-3’ and 5’-GTTCTGCAAACTTTTCAATCATTG-3’), BNA1 (5’-GCGTCAGGATAAATTGTGAGTCAC-3’ and CCTTCGTTCTCCTTCAACCATTTG-3’), HSP12 (5’-AAGCACTCTAGACGGAGAGTAACTAG-3’ and 5’-GAATCCTTTTCTACCTGCGTCAG-3’), HSP26 (5’-CGGATCTATGCACGTTCTTGAGTG-3’ and 5’-CCTTCACCCAGCAATCTGTTAAAG-3’).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Vancura’s group showed that Plc1 and IPs are involved in regulation of activity of the kinetochore by facilitating recruitment of another chromatin remodeling complex, RSC, which stands for Remodels Structure of Chromatin. RSC has been shown to be required for maintaining the structure of the centromere and for proper kinetochore function (Cairns et al, 1996; Desai et al, 2009). …”
Section: Biological Roles Of Ip and Pp-ip Molecules In Yeastmentioning
confidence: 99%
“…Loss of Sth1p/Nps1p function results in reduced histone occupancy around the centromere by nucleosome-scanning assay and chromatin immunoprecipitation (Desai et al , 2009) and leads to cell cycle arrest at G2/M. Nucleosomes flanking the centromere are subject to disruptive tension from the spindle, which would require removing mislocalized nucleosomes and reloading them in the proper position.…”
Section: Introductionmentioning
confidence: 99%